New directions in the mental health care of migrants, including refugees—A randomized controlled trial investigating the efficacy of value‐based counselling. (30th March 2022) - Orang, Tahereh Mina; Missmahl, Inge; Thoele, Anna‐Maria; Valensise, Livia; Brenner, Anna; Gardisi, Maryam; Peter, Helmut; Kluge, Ulrike
Abstract: Objective: Specialized literature has identified a need for evidence‐based, low‐threshold, short‐term, and intracultural psychological interventions that can be made available to migrants, including refugees, who suffer from psychological symptoms in host countries. The objective of the present study is to measure the efficacy of value‐based counselling (VBC) as such an intervention. Method: We conducted a pragmatic, rater‐blinded randomized controlled trial employing a pre‐post control group design to assess the efficacy of VBC based on a study sample of 103 migrants, including refugees, who resided in Germany at the time. A set of instruments was used to evaluate primary outcome measures of depression, posttraumatic stress disorder (PTSD) symptoms, perceived stress, generalized anxiety, and somatic complaints. Results: Per protocol analysis included 42 participants in the VBC group, and 43 in the waiting list. Compared with participants in the waiting‐list group, the VBC group, following an average of four counselling sessions, experienced a clinically meaningful reduction of depression (adjusted difference 7.06, 95% CI [4.86, 9.26], effect size 0.68, p < .001), PTSD (adjusted difference 17.15, 95% CI [10.49, 23.81], effect size 0.76, p < .001), perceived stress (adjusted difference 9.25, 95% CI [6.23, 12.27], effect size 0.75, p < .001), anxiety (adjusted difference 5.34, 95% CI [3.47, 7.20], effect size 0.70, p < .001), and somatic complaints (adjusted difference 5.52, 95% CI [3.30, 7.74], effect size 0.72, p < .001). The positive outcomes were maintained at 3‐month follow‐up. Utilization of mental health services was significantly reduced at the 3‐month follow‐up conducted with participants of the VBC group. Conclusions: VBC, a culturally sensitive and strength‐based mental health service, is an effective short‐term intervention which meets the specific mental health needs of migrants, including refugees.